Publishing plan & pilot issue of a publication for senior citizens in Singapore. - Tan, Phila Anne. (2011)
The project consisted in the main of the production of a publishing plan and the pilot issue of a new publication for senior citizens in Singapore. The project centred on the 'greying of the population', a fundamental social phenomenon of the next century. The project addressed the challenges of the greying issue in Singapore. The number of Singaporeans aged 60 years and above is set to increase from one in ten currently to one in four over the next 30 years. Recognising that this demographic trend has socio-economic impact and implications to society, attention to the issue has been paid by the government, policy makers as well as the media.